Work ability psychological variables in workers of the pharmaceutical industry : The importance of internal marketing - De Almeida, Hugo; Gomes, Ana; Bem-Haja, Pedro; Brito-Costa, Sónia (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Internal Marketing is also positively related to job satisfaction. However, there is a gap in the literature on the influence of Internal Marketing (IM) on Work Ability (WA) in the workers of the Pharmaceutical Industry. The aim of our study is to assess this interaction, demonstrating evidence that the Internal Marketing’s five dimensions affect, positively or negatively the WA in workers of the Pharmaceutical Industry. Methods: We collected data (N = 150) from workers of Pharmaceutical Industry mean age of 37.86 years (SD=10.788), through internal advertisements at the university posted on information dissemination panels, e-mail databases and through the social LinkedIn network. The Statistical Package R-Studio program was used for statistical analysis. Results: We verified that the group with Poor WA had a lower average value of Perceived IM than the group with Good WA. Conclusions: This study seems to indicate that promoting IM protocols helps increase WA among pharmaceutical industry workers.